IMPLEMENTASI KEBIJAKAN PENATAAN RUANG TERBUKA HIJAU - ', Hayat ' (Jurnal Ilmu Administrasi Negara, 2014)
Implementation of Planning Policy Green Open Space. This study aims to determine the implementation of the arrangement of green open space (RTH) in Malang and its impact on the development of Malang City, was based Malang Regional Regulation No. 7 Year 2001 on Spatial Planning Malang. Descriptive research method uses quantitative methods. Samples were taken as many as 40 people using purposive sampling technique. Techniques of data collection using questionnaires, interviews, and documentation. Data analysis techniques used the frequency table generated from the source data taken using a percentage according to the indicators evaluated. The results showed that the arr0angement of the Malang City green open space is still less appropriate to use, needs, grouping, management, and development. The implications of the research needed serious attention and good cooperation for memathui rules and regulations associated with RTH. Need to be a maintenance and preservation of green space where a growing number of community needs clean environment, healthy and comfortable. Keywords: spatial planning, urban green space, the implementation of the policy.